Advances on delta 5-unsaturated-polymethylene-interrupted fatty acids: Resources, biosynthesis, and benefits. Issue 6 (9th July 2021) - Song, Lili; Wen, Sisi; Ye, Qin; Lou, Heqiang; Gao, Yadi; Bajpai, Vivek K.; Carpena, María; Prieto, Miguel-Angel; Simal-Gandara, Jesus; Xiao, Jianbo; Meng, Xianghe; Wu, Jiasheng
Abstract: Though the knowledge on delta 5-unsaturated-polymethylene-interrupted fatty acids (Δ5-UPIFAs) is being updated, the issue of their integration still exists within the field. Thus, this review systematically summarizes the sources, biosynthesis and metabolism, analytical methods, preparation, and health-promoting roles of Δ5-UPIFAs. In plants, the content of Δ5-UPIFAs is higher, which is an ideal source. In animals, although the content of Δ5-UPIFAs is not high, there are many species, which is the possible source of some special Δ5-UPIFAs. At present, although the extraction of Δ5-UPIFAs is mainly from plants, the fermentation by organisms, especially for genetically modified microorganisms engineering maybe be a substitue of pepration of Δ5-UPIFAs. Δ5-UPIFAs have been proved to possess multi-beneficial effects, such as lipid lowering, anti-inflammation and so on, so it has a certain potential application value. However, related knowledge of the underlying molecular mechanisms regarding Δ5-UPIFAs limited, and how Δ5-UPIFAs work is not clear. Further clinical and human studies about Δ5-UPIFAs are also needed. Studies on tapping new resources, developing structured lipide rich in Δ5-UPIFA and enhancing delivery were quite deficient. This review emphasizes the further directions on Δ5-UPIFAs with scientific suggestions to pay more attention to the applications of Δ5-UPIFAs in food, pharmaceutical and cosmetic industries.